Effect of environmental variables on epiphyton in a pampean lake with stable turbid-and clear- water states - Cano, Maria Gabriela (2012)
In the present study, we examined the variation in composition and biomass of epiphyton growing on the bulrush Schoenoplectus californicus in a pampean lake that passed through a turbid- and a clear-water period within an annual cycle. Monthly sampling was performed year-round at the center and periphery of a bulrush stand. We measured the physicochemical parameters in the water column using standardized field and laboratory methods. The epiphyton was sampled by sectioning bulrush stems into segments for pigment analysis, abundance measurements, and biovolume quantification. Two different types of communities were observed during the annual cycle. In the turbid-water period, epiphyton biomass and diversity remained low despite sufficient levels of phosphates. An abrupt increase in epiphyton biomass, along with structural changes in the community, occurred after an improvement in water transparency, suggesting that the epiphyton was strongly dependent on underwater light conditions. Differences in epiphyton composition and biomass between the center and the periphery of the bulrush stand were negligible. We conclude that the availability of colonizing surface is not a relevant driver for the colonization and growth of these epiphyton assemblages. The epiphyton in pampean lakes may remain stable and resilient for relatively long periods, even when confronted with environmental perturbations, and changes in these communities will only occur in relation to radical alterations in light and nutrient availability.